Encouraging State Governments to Protect and Restore Forests Using Ecological Fiscal Transfers: India's Tax Revenue Distribution Reform. Issue 2 (24th October 2017) - Busch, Jonah; Mukherjee, Anit
Abstract: In February 2014, India's 14th Finance Commission added forest cover to the formula that determines the amount of tax revenue the central government distributes annually to each of India's 29 states. The Government of India estimates that from 2015 to 2019 it will distribute $6.9–$12 billion per year to states in proportion to their 2013 forest cover, amounting to around $174–$303 per hectare of forest per year. Assuming that contemporary forest cover will remain an element of the formula beyond 2020, Indian states now have a sizeable new fiscal incentive to protect and restore forests, contributing to the achievement of India's climate goals. India's tax revenue distribution reform creates the world's first ecological fiscal transfers (EFTs) for forest cover, and a potential model for other countries. In this article, we discuss the origin of India's EFTs and their potential effects. In a simple preliminary analysis, we do not yet observe that the EFTs have increased forest cover across states, consistent with our hypothesis that 1 to 2 years of operation is too soon for the reform to have had an effect. This means there remains substantial scope for state governments to protect and restore forests as an investment in future state revenues.